22q11 deletion syndrome: is that what they used to call...? - Umlauf MG (Perspectives in Psychiatric Care, 2008)
PURPOSE. 22q11 deletion syndrome (22q11DS) is a very common, but commonly overlooked, disorder that has many viariable features, such as serious heart defects, speech and articulation problems, immune compromise, learning problems, pervasive developmental disorders, and a late appearing phenotype of this condition-mental illness. CONCLUSION. Persons with 22q11DS are likely to be medically complex patients with pervasive developmental disorders and late appearing mental problems. PRACTICE IMPLICATIONS. Establishing this diagnosis is useful to families and healthcare providers to anticipate and address immediate and future issues surrounding health promotion, disease prevention, and health maintenence.